Pengaruh Corporate Governance dan Karakteristik Perusahaan Terhadap Praktik Pengungkapan Laporan Tahunan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Fella Novita Ariyanti; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
This study aims to obtain empirical evidence about the influence of corporate governance and company characteristics on the disclosure practices of firms. Elements of corporate governance that are used to test the disclosure practices of firms consist of the proportion of independent commissioners, audit committee independence, audit committee competence and ownership structure. The firm characteristics factors that used in this study such as firm size, and leverage. Retrieval of data in this study using purposive sampling method in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the year 2011-2013. The samples of this study as many as 91 companies, and for the items disclosure take from research of Francis Aboagye-Otchere, et al (2012). The data of this study were tested using multiple regression analysis. The empirical result of this study show that the proportion of independent commissioners, firm size, and leverage are significant and positive effect to the disclosure practices of firms in Indonesia. While, audit committee independence, audit committee competence and ownership structure has no significant impact on disclosure practices of firms.